Ultrasonographic evaluation of abnormal uterine bleeding in postmenopausal women - Kadakola, Bindushree; Gurushankar, G.; Shivamurthy, Geetha; Rashmi, M. N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objectives of current study were to diagnose causes of Abnormal Uterine Bleeding (AUB) in postmenopausal women (PMW) and to correlate it with curettage and histopathological findings, hysteroscopy and thereby minimizing unnecessary interventions in the form of operations and hysteroscopy where sonography depicts normal findings. Methods: After obtaining ethical clearance present prospective observational study was conducted from November 2010 to November 2012, to evaluate the endometrium in 50 postmenopausal women (PMW) with bleeding per vagina referred to the department of Radio diagnosis by the department of gynaecology in Bangalore medical college and research institute. After applying inclusion and exclusion criterias the cases were evaluated with ultrasonography both transabdominal (TAS) and transvaginal scan (TVS where ever necessary). Histopathological and hysteroscopic correlation was done in all cases. Results: 58% of the PMW with bleed were in the age group of 51-60 years. Most common cause of PMB was atrophic endometrium (44%), endometrial polyp (22%), followed by malignancy (14%), and hyperplastic endometrium (6%). At Endometrium thickness less than 4 mm there were nil chances of carcinoma. Conclusions: In women with AUB in postmenopausal age ultrasonography (USG) can be considered as an initial imaging modality for diagnosing endometrial diseases. The sensitivity and specificity of USG for Atrophic endometrium is 100% & 84% respectively with accuracy of 100%, endometrial polyp the specificity is 100% with accuracy of 88%. For malignancy USG showed 100% specificity & accuracy of 100%. Hence USG is highly accurate for evaluating endometrial pathologies. Being noninvasive, less costly & good patient compliance USG should be considered as an initial imaging modality over invasive investigations like D&C, hysteroscopy in evaluating endometrial disorders.